Respostas

2014-08-30T21:39:46-03:00
4+x(x-4)=x
4+x²-4x=x
x²-4x-x+4-0
x²-5x+4=0

Δ = b² - 4.a.c
Δ = -5² - 4 . 1 . 4
Δ = 25 - 4. 1 . 4
Δ = 9

x = (-b +- √Δ)/2a
x' = (--5 + √9)/2.1       x'' = (--5 - √9)/2.1
x' = 8 / 2                    x'' = 2 / 2
x' = 4                         x'' = 1
2 5 2
A melhor resposta!
2014-08-30T21:46:13-03:00
4+x(x-4)=x
4+x elevado a dois - 4x=x
4+ x elevado a dois -4x-x=0
x elevado a dois -5x+4=0
a=1
b=-5
c=4
Δ=b elevado a dois -4ac
Δ=-5 elevado a dois-4.1.4
Δ=25-16
Δ=9
x=-b+-√Δ/2a
x=5+-3/2
x=5+3/2 x=8/2 x=4
x=5-3/2 x=2/2 x=1


entao os resultados das equacoes e 4 e 1 ok
3 5 3